Measurement procedure for the assessment of specific absorption rate of human exposure to radio frequency fields from hand-held and body-mounted wireless communication devices. Human models, instrumentation, and procedures (Frequency range of 4 MHz to 10 GHz) Part 1528, (17th December 2021) - British Standards Institution,
No abstract available